2015
DOI: 10.1002/ca.22548
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the humeral insertion of the supraspinatus and infraspinatus tendons: Application to rotator cuff repair

Abstract: In shoulder surgery, a precise understanding of anatomical relationships is required for accurate reconstruction. Reports in recent literature have challenged the traditional definitions of the humeral footprints of the supraspinatus and infraspinatus tendons. This study aims to precisely delineate these footprints. The rotator cuffs of 54 shoulders from 27 Australian Caucasoid donor cadavers were examined. The tendinous portions were dissected down to their region/footprint of attachment upon the humerus. Mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
(45 reference statements)
1
10
0
Order By: Relevance
“…Sociodemographic variables such as gender, dominant arm, age, and BMI were evaluated. A statistically significant difference for these variables was not found regarding SMT location, which matches previous studies related to palpation and location of anatomic structures [33,34]. However, weight showed statistically significant differences, even if BMI did not (p =.02).…”
Section: Discussionsupporting
confidence: 87%
“…Sociodemographic variables such as gender, dominant arm, age, and BMI were evaluated. A statistically significant difference for these variables was not found regarding SMT location, which matches previous studies related to palpation and location of anatomic structures [33,34]. However, weight showed statistically significant differences, even if BMI did not (p =.02).…”
Section: Discussionsupporting
confidence: 87%
“…Footprint measurement after preparation for RC reinsertion in the greater tuberosity is a more reliable value that is unaffected by the age, sex, height, size, or position of the patient. 26 Measurements exceeding footprint exposure by 2.5 cm indicate that the supraspinatus is fully involved as well as at least 50% of the infraspinatus. On the other hand, despite moderate reliability in terms of interobserver assessments of retraction and fat degeneration on MRI (Patte and Goutallier), 24 there is a consensus regarding a poorer prognosis in patients with Patte grade 2 or 3 and Goutallier grade 3 or 4 during midterm clinical and structural follow-up.…”
Section: Discussionmentioning
confidence: 98%
“…Recent reports questioned the conventional definitions of the humeral footprints of the SSP and ISP tendons. 10,11 According to the traditional theory, the location 13 to 17 mm posterior to the biceps tendon is recognized as the entire part or portion of the SSP tendon. 4,13 However, a recent anatomic study by Mochizuki et al 11 reported findings in contrast with what previous studies had demonstrated.…”
Section: Discussionmentioning
confidence: 99%